1981
DOI: 10.1017/s0025315400048177
|View full text |Cite
|
Sign up to set email alerts
|

Responses ofcorophium volutatorto sediment sulphide

Abstract: An apparatus has been developed which allows the complete replacement of interstitial water in sediments without disturbance. In principle, it can be adapted to handle sand or mud, different solutions, and different volumes of sediment. The apparatus was tested with 0·05% (wt/vol.) eosin in sea water. After replacement of the interstitial water, the eosin was evenly distributed throughout the sediment. Interstitial water in samples of sediment was replaced by sulphide solutions in sea water, at a range of conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
2

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 15 publications
0
9
0
2
Order By: Relevance
“…Meadows [1][2][3] previously examined the preferred habitat of Corophium volutator in the field, investigating variables such as depth selection, particle size, temperature, salinity, and biofilm. Additional biological studies have been undertaken worldwide since and increase our ecological knowledge of this species [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Meadows [1][2][3] previously examined the preferred habitat of Corophium volutator in the field, investigating variables such as depth selection, particle size, temperature, salinity, and biofilm. Additional biological studies have been undertaken worldwide since and increase our ecological knowledge of this species [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…In some environmental samples, violation of the criteria may have a natural cause (reduced oxygen level in some sediments, low pH values in peaty samples, etc. ), while in samples from polluted areas several other important variables may also exceed the thresholds (e.g., ammonia, sul"de, salinity; e.g., Jacobs et al, 1992;Meadows et al, 1981;Thompson et al, 1991;Wang and Chapman, 1999). These variables are often called &&confounding factors,'' since these variables interfere with biological e!ects of micropollutants.…”
Section: Introductionmentioning
confidence: 99%
“…Cunha and Moreira (1995) showed that, in summer, when dense vegetation and high temperatures occur, the oxygen concentrations, which reached oversaturation during the day in AreaÄ o, are followed by a drastic drop during the night (»2 mg l )1 ; 15 to 30% saturation). Physiological sensitivity of Corophium species to some factors such waste discharges, sulphide, and hypoxia has been mentioned or demonstrated by several authors (SegestraÊ le 1959; Meadows et al 1981;Esselink et al 1989;Gamenick et al 1996). However, other studies failed to establish any correlation between local distribution and abiotic factors (Murdoch et al 1986;O Â lason and Persson 1986;Jensen and Kristensen 1990;Hughes and Gerdol 1997).…”
Section: Environmental Factorsmentioning
confidence: 96%